If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 3x = 5x + 2 Reorder the terms: 2 + 3x = 2 + 5x Add '-2' to each side of the equation. 2 + -2 + 3x = 2 + -2 + 5x Combine like terms: 2 + -2 = 0 0 + 3x = 2 + -2 + 5x 3x = 2 + -2 + 5x Combine like terms: 2 + -2 = 0 3x = 0 + 5x 3x = 5x Solving 3x = 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 3x + -5x = 5x + -5x Combine like terms: 3x + -5x = -2x -2x = 5x + -5x Combine like terms: 5x + -5x = 0 -2x = 0 Divide each side by '-2'. x = 0 Simplifying x = 0
| 1800-279x=3450 | | 23x+2y=164 | | y=2x+52 | | 119=-3(1+5k)+2 | | (x)(3x)=75 | | 14x+8=x^2 | | x+13=x+1 | | -9d-5+8+7d= | | -5x^2=-160 | | f(x)=-12x+8 | | 2(4a-1)=3(a+2) | | 9-13x-5-2x=7 | | 3x^3-25x^2+53x-15=0 | | 279x+1800=3450 | | -138=6(1-6x) | | 11x=2x^2-6 | | N=14+5q | | 6(5x-3)=102 | | 12x+9y=9y | | 3b-8(2b-3)=102 | | 9-c^2= | | 2x^2=756 | | 10x-7=91-4x | | 3x+-1=-32 | | 3(-4-9n)-6n= | | 84=6(2-x)-3x | | -2=-2(n-8) | | 7(-4-5p)-4=-207 | | 5x+4-7x=5+x+13 | | 29+2x=x+25 | | 8-3y=-4 | | 4x^3+x^3+9x^2=0 |